The Effectiveness of Digital Consumer Protection Law in Promoting Trust and the Growth of Online Economic Transactions - Kriswandaru, Althea Serafim; Fachuda, Fatimah Azzahro; Risma, Siti Sya'ada Alda (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The development of the digital economy in Indonesia presents both opportunities and challenges that materially affect the effectiveness of legal protection for digital consumers. This study aims to examine the impact of digital consumer protection legislation on consumer trust and its subsequent effect on the growth of online economic transactions. A quantitative approach was employed, surveying 400 active digital consumers in Indonesia using an online survey, and analyzed using multiple linear regression. The results indicate that the effectiveness of laws, especially with respect to regulatory clarity and personal data protection, poses a significant positive influence on consumer trust. Thus, it can be argued that trust drives consumers' intentions to continue digital transactions, leading to the continuous, sustainable growth of the digital economy. At the heart of this research is the legal-and-consumer-behavior approach integrated into an empirical model, with primary focus on the under-researched topic in Indonesia. Practically, this result provides a good platform for consumer-facing policymakers who want to design adaptive regulations and nudge businesses into adopting compliance as a strategy in their efforts to build digital consumer loyalty.